HUBUNGAN TINGKAT KECUKUPAN GIZI, ASUPAN TEMBAGA, SERAT DAN FITAT DENGAN KADAR SENG SERUM ANAK SEKOLAH DASAR BERTUBUH PENDEK DI KARANGAWEN DEMAK - Santi Rahayu; Hertanto Wahyu Subagio; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Background : Zinc deficiency cause of some inadequate function of the body such as slowed growth and recuce development children. Many factor affect the absorption and excretion zinc in the body that increase risk of zinc deficiency, likes infection disease, physical condition, dan diet factor. Nutrient and phytate in food influences zinc absorption. Objective.' Purpose of this research is to know relation between nutrient and phytate with zinc serum level.Method .' crosss sectional observasional design with cross sectional method. 1 13 Sampel for research are 1 " and 2 "d grade elementary school student at Karangawen, Demak who has stunted nutrition status (based on height-for-age < -2 to Z point WHO-NCHS score). Secondary data gained from food frequency semiquantified and result of zinc serumlevel from laboratorium assessment. Data analysis used Pearson Product Moment test. Resalt.' From data analyze got significant correlation between adequacy rate of vitamin A, dietary fiber intake phytate intake and copper intake with zinc serum level (p < 0,05). Otherwise no significant correlation adequacy rate of protein, and adequancy rate of ironwith zinc serum level. (p > 0,05).Conclusion .'Used the other different measurement zinc level method in order to minimize weakness and complete each other.Key words: Stunted Elementary School Student, Serum zinc level, Copper, phytate intake.